Application Of Digital Tourism Technology In Efforts To Increase The Tourism Attractiveness Of Kampung Batik Laweyan Surakarta City - Yuliatmojo, Widyantoro; Maharani, Ariza Fitria (Sean Institute, 2024)
Surakarta is famous for its many interesting attractions, ranging from culture, history, to culinary. One of the destinations that should not be missed is Kampoeng Batik Laweyan, a cultural heritage and famous batik home industry tour in Indonesia. As a favorite tourist destination for local and foreign tourists, Kampoeng Batik Laweyan continues to innovate by utilizing digital technology. This effort was made by Kampoeng Batik Laweyan Development Forum (FPKBL) to increase tourist attraction. The author uses descriptive research with a qualitative approach. This research examines how the application of digital tourism technology in Kampoeng Batik Laweyan. The results show that FPKBL utilizes various digital platforms, such as websites and social media, to provide the latest information about Kampoeng Batik, including contact persons to facilitate communication with visitors. The application of digital technology has proven to be effective in increasing the tourism attractiveness of Kampoeng Batik Laweyan. It shows that the combination of tradition and digital innovation can be the key to success in developing an attractive and sustainable tourist destination.